2021
DOI: 10.1002/1878-0261.13074
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 promotes inflammatory breast cancer tumorigenesis and skin invasion

Abstract: Inflammatory breast cancer (IBC) is an aggressive form of primary breast cancer characterized by rapid onset and high risk of metastasis and poor clinical outcomes. The biological basis for the aggressiveness of IBC is still not well understood and no IBC-specific targeted therapies exist. In this study we report that lipocalin 2 (LCN2), a small secreted glycoprotein belonging to the lipocalin superfamily, is expressed at significantly higher levels in IBC versus non-IBC tumors, independently of molecular subt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 58 publications
1
20
1
Order By: Relevance
“…Previous studies have suggested that LCN2 promotes breast cancer progression by enhancing migratory and invasive capabilities of breast cancer cells (24, 25). On account of the substantial LCN2 upregulation we detected in cells treated with senescent CM, we hypothesize that the SASP enhances aggressive breast cancer phenotypes at least in part through upregulation of LCN2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that LCN2 promotes breast cancer progression by enhancing migratory and invasive capabilities of breast cancer cells (24, 25). On account of the substantial LCN2 upregulation we detected in cells treated with senescent CM, we hypothesize that the SASP enhances aggressive breast cancer phenotypes at least in part through upregulation of LCN2.…”
Section: Resultsmentioning
confidence: 99%
“…3D). The most significantly enriched genes in D2.0Rs upon docetaxel treatment were known protumor genes such as Fth1, Lcn2, Cxcl5, Tubb5, Tuba1a, Tubb4b and Hmox1 , which have been implicated in chemo-resistance (21, 26, 27), breast cancer tumorigenesis (23), invasiveness, metastatic colonization (24) and cancer cell survival (22). IPA revealed several upstream activated regulatory molecules in cancer cells including Hras, Myc, Mek , etc.…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3B shows the top 20 upregulated genes in DTX and VEH organoid datasets, wherein genes associated with autophagy induced dormancy (Col1a1, Stmn1) and tumor suppression (Tpi2, Tpm2) were enriched in VEH group (18)(19)(20), while genes associated with chemoresistance (Fth1, Hmox1), breast cancer tumorigenesis (Lcn2), cancer proliferation and invasiveness (Cxcl5, Spp1) were enriched in DTX group (21)(22)(23)(24)(25). Ingenuity pathways analysis (IPA) of pathways associated with DTX treatment enriched transcripts demonstrated activation (z-score > 1) of multiple pathways related to cancer pathogenesis, cytokine signaling, cell proliferation and anti-apoptosis, etc.…”
Section: Transcriptomic Analysis Revealed Involvement Of Mek Signalin...mentioning
confidence: 99%
“…Based on our nding, m5C of MMP9 gene may take part in brain metastasis but the complete mechanism still needs to be further studied. LCN2 (Lipocalin 2), signi cantly predicts MMP9 levels in women with breast cancer [58], is involved in the epithelial-to-mesenchymal transition, angiogenesis, and cell migration and invasion in breast cancer [59].…”
Section: Discussionmentioning
confidence: 99%